PERAN WAKIL RAKYAT DALAM PEMBANGUNAN DI DAERAH PEMILIHAN SUMENEP - Hidayaturrahman, Mohammad (JURNAL SOSIAL POLITIK, 2020)
This research was conducted to find out how the role of people's representatives in fighting for the aspirations of the people represented based on electoral districts (Dapil) in development. This research uses descriptive qualitative method, by collecting data through direct observation in the field (observation) and in-depth interviews (in-depth interviews) with various informants related to the study. The rationale in this research is the theory of political representation (representation), which analyzes how the roles, duties and functions of people's representatives. From the results of the study found the role of people's representatives who fight for the aspirations of the community in the form of escorting grant assistance programs to community groups, both social and empowerment (budgeting function). Besides other forms of role carried out by the people's representatives is the function of supervision (control) of government programs, such as the implementation of the distribution of rice to prosperous families (rastra), the implementation of construction of school buildings, and others. The role of board members who are still not maximized is related to the function of the budget (budgeting), especially in the field of infrastructure. This is clearly seen from the unfinished construction of road infrastructure and health infrastructure in the Kangean Islands and Sapeken areas.